Status of the atomic fountain clock at the National Research Council of Canada. (June 2016) - Beattie, S; Alcock, J; Jian, B; Gertsvolf, M; Bernard, J
Abstract: Despite the rapid advances in optical frequency standards, caesium fountain clocks retain a critical role as the most accurate primary frequency standards available. At the National Research Council Canada, we are working to develop a second generation caesium fountain clock. Work is currently underway to improve several systems of FCs1, such as the laser system and microwave local oscillator, which will be incorporated into its refurbished version, FCs2. In addition, we have added an optical pumping stage which has increased the detected atom number by over a factor of six. In collaboration with the National Physical Laboratory (NPL), we are planning on replacing the physics package of FCs1. We will report on several recent improvements to FCs1, along with our progress in the development of FCs2.